2020
DOI: 10.1161/circep.120.008686
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic QT Intervals in Infants Exposed to Hydroxychloroquine Throughout Gestation

Abstract: Background - Based on inhibition of viral replication and limited reports on clinical efficacy, hydroxychloroquine (HCQ) is being considered as prophylaxis and treatment of COVID-19. Although HCQ is generally considered safe during pregnancy based on studies in patients with systemic lupus erythematous and other rheumatic conditions, there may still be reluctance to institute this antimalarial during pregnancy for the sole purpose of antiviral therapy. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
1
12
0
4
Order By: Relevance
“…Then, Jaeggi et al ( 60 ) reported that in a Canadian cohort 116 anti-Ro/SSA-positive newborns/infants without aCHB, transient QTc prolongation was rather frequent, it being present in 15% of cases ( 60 ). Consistent data were more recently obtained by Friedman et al ( 62 ) who analyzed the ECGs of 45 infants without aCHB born from anti-Ro/SSA-positive mothers and found that QTc prolongation > 2 standard deviations above historical healthy controls was present in 11% of subjects. Moreover, AlTwajery et al ( 61 ) demonstrated that among 41 children affected with SLE, anti-Ro/SSA-positivity was associated with a higher prevalence of ECG abnormalities, particularly QTc prolongation > 450 ms.…”
Section: Anti-ro/ssa-associated Long-qt Syndromesupporting
confidence: 89%
“…Then, Jaeggi et al ( 60 ) reported that in a Canadian cohort 116 anti-Ro/SSA-positive newborns/infants without aCHB, transient QTc prolongation was rather frequent, it being present in 15% of cases ( 60 ). Consistent data were more recently obtained by Friedman et al ( 62 ) who analyzed the ECGs of 45 infants without aCHB born from anti-Ro/SSA-positive mothers and found that QTc prolongation > 2 standard deviations above historical healthy controls was present in 11% of subjects. Moreover, AlTwajery et al ( 61 ) demonstrated that among 41 children affected with SLE, anti-Ro/SSA-positivity was associated with a higher prevalence of ECG abnormalities, particularly QTc prolongation > 450 ms.…”
Section: Anti-ro/ssa-associated Long-qt Syndromesupporting
confidence: 89%
“…Friedman et al show no correlation between cord blood levels of HCQ and neonatal corrected QT interval (QTc) after analyzing 45 neonatal ECGs (R = 0.02, p = 0.86). Only 5 neonates in Friedman's study, 11% of the population had prolonged QTc above 2 SD when compared with historical healthy controls but ECGs were otherwise unremarkable [17].…”
Section: Discussionmentioning
confidence: 87%
“…Prolonged QTc was also reported in an open-label single-arm study in 5/45 (11%) infants from the gestation of pregnant mothers taking HCQ. Still, they were asymptomatic, and there was no correlation with maternal or cord HCQ levels (Friedman et al, 2020). In contrast, two observational studies using the hospital database in the New York region showed that the used of HCQ, azithromycin, or both, compared with no treatment, was not significantly differences in in-hospital mortality, and none of patients was found to have an abnormal electrocardiogram.…”
Section: Introductionmentioning
confidence: 87%